Threshold effects of the relationship between physical exercise and cognitive function in the short-sleep elder population - You, Yanwei; Chen, Yuquan; Chen, Xiangyu; Wei, Mengxian; Yin, Jiahui; Zhang, Qi; Cao, Qiang (Frontiers in aging neuroscience, 2023)
It has been demonstrated that elderly people's cognitive capacities can be improved with exercise, and short sleep is linked to cognitive decline. However, the impact of physical exercise on cognitive performance in seniors who do not get enough sleep is largely unknown. This makes it an intriguing subject to explore further. This study consisted of elders (over 60 years old) who participated throughout the National Health and Nutrition Examination Survey's 2011-2014 cycle (NHANES). Weighted linear regression model and restricted cubic splines analysis were performed to evaluate the association between physical exercise and cognitive function. In the end, 1,615 samples were scrutinized and the total number of weighted respondents was 28,607,569. Results showed that in the Animal Fluency test and the Digit Symbol Substitution test, a positive association was found between physical exercise volume and scores in the fully adjusted model. A two-piecewise linear regression model was then applied to explore the threshold effect of exercise on cognitive performance. Before 960 and 800 MET-minutes/week, there were consistent positive relationship between exercise and scores of the Animal Fluency test [ß (95% CI): 0.233 (0.154, 0.312), < 0.001] and Digit Symbol Substitution test [β (95% CI): 0.555 (0.332, 0.778), < 0.001], respectively. However, there was a saturation effect where physical exercise volume reached the two inflection points. According to our research, the benefit of exercise did not always expand with the exercise volume increment under the short-sleep condition, which challenged existing knowledge. The short-sleep elder group could maintain cognitive performance with no more than 800 MET-minutes/week of physical exercise. Verification of these findings requires further biological investigations.